2013
DOI: 10.1158/1535-7163.mct-12-0672
|View full text |Cite
|
Sign up to set email alerts
|

Reversing Effect of Ring Finger Protein 43 Inhibition on Malignant Phenotypes of human Hepatocellular Carcinoma

Abstract: It has been shown that Ring finger protein 43 (RNF43) is overexpressed in colorectal cancer and mediates cancer cell proliferation; however, its role in hepatocellular carcinoma (HCC) remains unknown. In this study, we found that RNF43 was frequently overexpressed in HCCs, and this overexpression was correlated with positive vascular invasion, poor tumor differentiation, and advanced tumor stage. Functional studies showed that knockdown of RNF43 could induce apoptosis and inhibit proliferation, invasion, colon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…In addition, several reports (33,34,48,49) and the COSMIC database have shown that somatic mutations in the RNF43 locus were also identified in tumor samples from the skin, ovary, breast, prostate, liver, pancreas, and large intestine, suggesting that RNF43 functions as a tumor suppressor in many tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several reports (33,34,48,49) and the COSMIC database have shown that somatic mutations in the RNF43 locus were also identified in tumor samples from the skin, ovary, breast, prostate, liver, pancreas, and large intestine, suggesting that RNF43 functions as a tumor suppressor in many tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The gene interaction network was constructed using a gene expression pattern scanner (GePS: http://www.genomatix.de/) as described previously (10). …”
Section: Methodsmentioning
confidence: 99%
“…At 1 h after nsPEF treatment, the treated survival cells at the same number were obtained to perform transwell assays based on transwell chambers (Millipore, USA), reflecting cell metastasis and invasion ability, as previously described [14]. …”
Section: Methodsmentioning
confidence: 99%
“…At 1 h after nsPEF treatment, the treated cells were obtained to determine single-cell apoptosis using the assay of TdT–dUTP Terminal Nick-end Labeling (TUNEL) with In Situ Cell Death Detection Kit (Millipore, USA) according to manufacturer’s instruction, as previously described [14]. …”
Section: Methodsmentioning
confidence: 99%